Factors Associated With the Development of Chronic Kidney Disease in Children With Congenital Anomalies of the Kidney and Urinary Tract - Isert, Saskia; Müller, Dominik; Thumfart, Julia (Frontiers in Pediatrics, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) are the most common cause of end-stage renal disease in children and adolescents. The diversity of the malformations summarized by CAKUT is high and there are numerous associated syndromes. The genetic background of these malformations remains unknown in the majority of cases. The aim of this study was to evaluate factors associated with the development of chronic kidney disease (CKD) and underlying genetic aberrations in children and adolescents with CAKUT. For this purpose, data from patients with CAKUT presented at the pediatric nephrology outpatient clinic were analyzed in a cross-sectional single-center study. Among the 405 patients, the commonest findings related to CAKUT were renal hypoplasia/dysplasia (65%), followed by hydronephrosis (43%). 44% of the patients were suffering from CKD, 6% were ranked as end stage renal disease. In the univariate analysis, male gender and premature birth were associated with higher CKD stages (p=0.004 resp. p<0.001). Children with an abnormal prenatal ultrasound had more often a glomerular filtration rate of less than 30 ml/min/1.73m² (p=0.004). Patients with urinary tract infections as first symptom whereas had significant lower CKD stages (p=0,006). In the multivariate analysis, premature birth (p=0.033) and urinary tract infection as first symptom (p=0.043) were significantly associated with CKD stage ≥II. Among the 16% of the children who have undergone genetic analyses the most frequent genetic aberration was a mutation in HNF1β-gene. These results can be used for the care of patients with CAKUT subject to factors associated with developing CKD.